Analisis Struktur Modal Optimal Perusahaan Sub Sektor Farmasi yang Terdaftar di BEI - Siti Aisah; Radia Purbayati; Rosma Pakpahan (Indonesian Journal of Economics and Management, 2022)
The optimal of capital composition is determined between Debt and Capital determining the capital structure policy, taking in accounts the company’s funding needs so as so to maximize from farm value, in the phamaceytical sub sector companes listed oh the IDX for priod 2014-2018, with secondary data from the financial reports of PT KimiaFarma, PT KalbeFarma, PT Industri Jamu dan Farmasi Sido MuncuI, PT TempoScan Pasific, PT Merck, PT Pyridam Farma. uses the cost of capital (COC) and weight aveage cost of capital (WACC). The result shows PT Industri Jamu dan Farmasi Sindo MuncuI was optimal in 2018,PT Tempo Scan Pasific was optimal in 2014, PT Merck Tbk was optimal in 2016 and PT Pyrida Farma was optimal in 2016. PT Kimia Farma and Kalbe Farma not optimal.